If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -54 + -8x + -12 = 7x + 30 + -6x Reorder the terms: -54 + -12 + 11x + -8x = 7x + 30 + -6x Combine like terms: -54 + -12 = -66 -66 + 11x + -8x = 7x + 30 + -6x Combine like terms: 11x + -8x = 3x -66 + 3x = 7x + 30 + -6x Reorder the terms: -66 + 3x = 30 + 7x + -6x Combine like terms: 7x + -6x = 1x -66 + 3x = 30 + 1x Solving -66 + 3x = 30 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -66 + 3x + -1x = 30 + 1x + -1x Combine like terms: 3x + -1x = 2x -66 + 2x = 30 + 1x + -1x Combine like terms: 1x + -1x = 0 -66 + 2x = 30 + 0 -66 + 2x = 30 Add '66' to each side of the equation. -66 + 66 + 2x = 30 + 66 Combine like terms: -66 + 66 = 0 0 + 2x = 30 + 66 2x = 30 + 66 Combine like terms: 30 + 66 = 96 2x = 96 Divide each side by '2'. x = 48 Simplifying x = 48
| 5u-43=9(u-7) | | 2(u+7)=-2u+30 | | 1.1(-0.3w+10)=7.7 | | 3=3(v+5)+3v | | p=2(3)+2(4) | | -6x+4(x-8)=-24 | | -4(3y)-5+3(5y+5)= | | -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 | | -5(-5z)=150 | | 4n+3=86 | | -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) | | (-4,3)M,=1/2 | | X/7=9=15 | | 2w=10+7w | | 3x^2-8xy+4y^2=6 | | 4x^2+378x-13631=0 |